High-gain amorphous selenium photomultipliers

JP2022548256A5Active Publication Date: 2025-02-17THE RES FOUND OF STATE UNIV OF NEW YORK +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022516297
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-12
Filing Date
2020-09-11
Publication Date
2025-02-17
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

Existing photomultiplier tubes (PMTs) are expensive, bulky, fragile, and unsuitable for magnetic fields, have poor quantum efficiency in the visible spectrum, cannot operate in the infrared region, and are not suitable for high-speed timing applications, while solid-state alternatives like avalanche photodiodes suffer from stochastic impact ionization and high noise.

Method used

A photomultiplier tube using a solid photoconductive film of amorphous selenium (a-Se) with non-insulating metal oxide hole-blocking layers, which are high-k materials, to achieve high gain and low dark current density, mimicking the behavior of conventional PMTs without their limitations.

Benefits of technology

The a-Se photomultiplier tube achieves high gain and low dark current density, operating at room temperature and reducing noise, making it a reliable solid-state alternative to vacuum PMTs for applications in astronomy, spectroscopy, optical communications, medical imaging, and quantum optics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A photomultiplier tube is provided that includes a solid photoconductive film composed of amorphous selenium (a-Se). In a-Se-containing photomultiplier tubes, a hole-blocking layer is provided to maximize gain and maintain low dark conductivity. The hole-blocking layer also achieves reliable and repeatable impact ionization without irreversible breakdown. The hole-blocking layer is a non-insulating metal oxide with a dielectric constant (k) greater than 10.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] government support This invention was made with government support under EB025300 awarded by the National Institutes of Health. The United States Government has certain rights in this invention.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 899,437, filed September 12, 2019, the contents and disclosure of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to photomultiplier tubes, and more particularly to photomultiplier tubes that include a solid photoconductive film composed of amorphous selenium (a-Se). [Background technology]

[0004] Efficient sensing and imaging of low light signals down to the single-photon level with true solid-state photomultiplier tubes has been pursued for many years, with widespread applications in astronomy, spectroscopy, optical communications, medical imaging, and the rapidly developing fields of quantum optics and quantum information science. However, the most popular commercial detector for low-light detection and for achieving high dynamic range and linear-mode operation remains the vacuum photomultiplier tube (PMT). PMTs operate based on the photoelectric effect.

[0005] Electrons can be promoted from the valence band to the vacuum level by energetic photons, then multiplied by the dynodes, and then collected by the anode. The main advantage of PMTs is their ultra-high gain (typically 10 5 ~10 8 ) and low excess noise. However, PMTs are expensive, bulky, fragile, cannot operate under magnetic fields, have poor quantum efficiency in the visible spectrum, cannot operate in the infrared spectral region, cannot be pixelated into 2D imaging arrays, and are not suitable for high-speed timing applications (such as recent advances in picosecond time-of-flight sensing).

[0006] Crystalline silicon (c-Si)-based avalanche photodiodes (reverse-biased pn or pn junction devices) also amplify photogenerated carriers via an impact ionization process. The difference is that in PMTs, only electrons are present and are multiplied by the dynode in a highly deterministic manner, whereas in crystalline semiconductors, both electrons and holes can undergo impact ionization avalanche in the high-field region. The latter impact ionization process is highly stochastic, resulting in "excess noise" at high gains. As the multiplication factor M is increased in an avalanche photodiode (APD) by increasing the electric field F, the avalanche gain fluctuations become progressively worse. According to McIntyre theory, the slope of M versus F is a strong function of the ratio k of the ionization rates of the two carriers, where 1 ≤ k < 0. The high k value in crystalline semiconductors contributes to uniformity and yield issues in APDs.

[0007] The concept of band structure engineering using multi-gain-stage semiconductor heterojunctions was proposed in the 1980s to ensure that only one carrier type (electrons or holes) undergoes impact ionization, thus resulting in more deterministic ionization behavior. In conventional APDs, carriers undergo a highly stochastic impact ionization process with uniform probability in a certain high-field region. By exploiting the conduction band discontinuity of the heterojunction, the ionization probability increases immediately after electrons enter the narrow-bandgap semiconductor from the wide-bandgap semiconductor, thereby resembling the behavior of the dynode in a phototransistor (PMT). However, without clear evidence that such an ideal modification of ionization characteristics was possible to produce k≈0, and because of the ultralow gain achieved in these multi-stage heterojunctions at low excess noise and optimal signal-to-noise ratios (SNRs), interest in the field of band structure engineering waned before truly convincing results were evident.

[0008] Another important development, which was the closest solid-state device to resembling the behavior of a conventional PMT, was the Rockwell Si-based SSPM, with its noiseless, non-Markovian branch and F=1. Traditionally, carriers in APDs undergo ballistic impact ionization through a process called the Markovian (i.e., memoryless) branch. Because carriers travel a very short distance (and for an extremely short time) for the next impact ionization, the avalanche process is independent of the phonon scattering history (and the history of steps required to accumulate sufficient kinetic energy for impact ionization). However, carriers in Si SSPMs experience a much smaller electric field; therefore, they must accelerate for a finite period before gaining sufficient kinetic energy for the next impact ionization event. This "delay time" is expected to reduce (and potentially eliminate) excess noise in such devices (i.e., an excess noise factor of approximately 1) because multiple scattering events and associated acceleration and deceleration result in averaging of the distance traveled over the finite delay time before impact ionization. Thus, the history of phonon scattering and energy / momentum relaxation events play a role in the non-Markovian bifurcation process in SSPM, resulting in internal averaging of the stochastic process and producing a noiseless deterministic gain. The Si SSPM is an impurity band avalanche device that can be operated at cryogenic temperatures (i.e., cooled to about 5 K) and count individual photons with wavelengths between 0.4 and 28 μm, making it an important device for use in low-background, near-to-mid-IR detection applications. The device has been shown to operate at 10 5 It also has an ultra-high single-carrier impact ionization gain of up to 1000 conduction electrons. The avalanche impact ionization process is noiseless in SSPMs with F=1. SSPMs, however, are very difficult to fabricate, have extremely low yields to ensure k=0, and operate at extremely low temperatures which severely limited their applications; therefore, the technology was eventually abandoned soon after its conception. [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] Runnerstrom et al., "Colloidal Nanocrystals Films Reveal the Mechanism for Intermediate Room Temperature Proton Conductivity in Porous Ceramics," J. Phys. Chem. C208, 122, 13624~13635 [Non-patent document 2] Arul et al., “Strong Quantum Confinement Effect In Nanocrystalline cerium oxide”, Mater. Lett. 2011, 65, 2635~2638 [Non-patent document 3] Ohshima et al., "Excess Noise in Amorphous Selenium Avalanche Photodiodes", Appl. Phys., Part 2 1991, 30, L1071~L1074 [Non-patent document 4] Abbaszadeh et al., "Investigation of Hole-Blocking Contacts for High-Conversion-Gain Amorphous Selenium Detectors for X-Ray Imaging," IEEE Trans., Electron Devices 2021, 59, 2403~2409 [Non-Patent Document 5] Park et al., "Avalanche-type High Sensitive Image Pickup Tube using an a-Se photoconductive target", Jpn. J. Appl. Phys. 2003, 42, L209~L211 Summary of the Invention [Means for solving the problem]

[0010] A photomultiplier tube is provided that includes a solid photoconductive film composed of amorphous selenium (a-Se). In the a-Se-containing photomultiplier tube, a hole-blocking layer is provided to maximize gain and maintain low dark conductivity. The hole-blocking layer also achieves reliable and repeatable impact ionization without irreversible breakdown. Furthermore, the a-Se-containing photomultiplier tube has low light scattering due to the reduced number of layers that make up the a-Se-containing photomultiplier tube.

[0011] The hole blocking layer is a non-insulating metal oxide having a high dielectric constant (k). By "high-k" it is meant that the metal oxide has a dielectric constant measured in a vacuum greater than 10. High-k metal oxide hole blocking layers provide an improvement over equivalent a-Se-containing photomultiplier tubes in which the high-k hole blocking layer is replaced with one of an insulating hole blocking layer, a non-stoichiometric non-insulating hole blocking layer, or a stoichiometric non-insulating hole blocking layer having a dielectric constant lower than that of the high-k hole blocking layer.

[0012] In one embodiment of the present invention, a photomultiplier tube having a high gain is provided. By "high gain" it is meant that the photomultiplier tube has a gain of 100 or greater. The photomultiplier tube of the present application also exhibits a low dark current density. By "low dark current density" it is meant that the dark current density is less than 1000 pA / cm, as measured at the onset of avalanche. 2 The dark current density is:

[0013] In one embodiment of the present invention, a photomultiplier tube includes an electron blocking layer disposed on a first electrode. An amorphous selenium solid photoconductive film is disposed on the electron blocking layer. A hole blocking layer is disposed on the amorphous selenium solid photoconductive film. In accordance with the present invention, the hole blocking layer comprises a non-insulating metal oxide. A second electrode is disposed on the hole blocking layer. In some embodiments, the photomultiplier tube of the present invention includes a passivation buffer layer sandwiched between the amorphous selenium solid photoconductive film and the hole blocking layer.

[0014] In some embodiments of the present invention, the electron blocking layer is in direct physical contact with the surface of the first electrode, the amorphous selenium film is in direct physical contact with the surface of the electron blocking layer, the hole blocking layer is in direct physical contact with the surface of the amorphous selenium film, and the second electrode is in direct physical contact with the surface of the hole blocking layer. In other embodiments of the present invention, the electron blocking layer is in direct physical contact with the surface of the first electrode, the amorphous selenium film is in direct physical contact with the surface of the electron blocking layer, the passivation buffer layer is in direct physical contact with the surface of the amorphous selenium film, the hole blocking layer is in direct physical contact with the surface of the passivation buffer layer, and the second electrode is in direct physical contact with the surface of the hole blocking layer.

[0015] In another aspect of the invention, there is provided a device, e.g., a photodetector or imager, comprising at least one photomultiplier tube including an electron blocking layer disposed on a first electrode, an amorphous selenium solid photoconductive film disposed on the electron blocking layer, a hole blocking layer disposed on the amorphous selenium photoconductive film, the hole blocking layer comprising a non-insulating metal oxide, and a second electrode disposed on the hole blocking layer.

[0016] In a further aspect of the present invention, a method for forming a photomultiplier tube is provided. In one embodiment, the method includes forming an electron-blocking layer disposed on a first electrode. An amorphous selenium solid photoconductive film is formed on the electron-blocking layer. A hole-blocking layer is formed on the amorphous selenium solid photoconductive film. In accordance with the present invention, the hole-blocking layer comprises a non-insulating metal oxide. A second electrode is formed on the hole-blocking layer.

[0017] In one embodiment, the hole blocking layer is formed by preparing a solution-processed material composed of metal oxide nanocrystals or perovskite, which is then deposited on the surface of the amorphous selenium solid photoconductive film at a temperature below the crystallization onset temperature of selenium. [Brief explanation of the drawings]

[0018] [Figure 1] 1 is a cross-sectional view of a high-gain a-Se photomultiplier tube in accordance with one embodiment of the present invention. [Figure 2] [Figure 2A] Electric field plots inside a vertical a-Se photomultiplier tube with different hole-blocking layers, one not of the present invention, using a SiO2 hole-blocking layer (k=4), note k=εr. [Figure 2B] Electric field plots inside a vertical a-Se photomultiplier tube with different hole-blocking layers, one of the present invention, using a CeO2 quantum dot hole-blocking layer (k=28), note k=εr. [Figure 2C] Electric field plots inside a vertical a-Se photomultiplier tube with different hole-blocking layers, one of the present invention, using a SrTiO3 hole-blocking layer (k=300), note k=εr. [Figure 3] FIG. 2B shows a plot illustrating the effective quantum efficiency for various a-Se photomultiplier tubes using a 15 μm thick a-Se solid photoconductive film and including different hole blocking layers as described in FIGS. 2A-2C. The plot shows that the avalanche gain field exceeds 80 V / μm and that the highest gain is achieved using a SrTiO hole blocking layer. [Figure 4] [Figure 4A] Cross-section and corresponding FIB-SEM of an a-Se-containing photomultiplier tube with a CeO2 quantum dot hole-blocking layer. [Figure 4B] TEM micrograph of CeO2 nanocrystals with an average particle size of 5.3 nm used in providing the CeO2 quantum dot hole-blocking layer shown in Figure 4A. [Figure 4C] Particle size distribution plot of the CeO2 nanocrystals shown in Figure 4B, with the inset showing a high-resolution TEM of a single CeO2 quantum dot with a lattice fringe d-spacing of 0.316 nm, corresponding to the (111) plane of cubic fluorite CeO2. [Figure 4D] Illustrates the operating principle of the avalanche a-Se photomultiplier tube of Figure 4A. [Figure 5][Figure 5A] XRD pattern of 14 nm CeO2 quantum dots with a bulk reference pattern of cubic fluorite crystal structure. [Figure 5B] XPS spectra of Ce3d3 / 2 and Ce3d5 / 2 deconvoluted using Gauss-Lorentz (Voight) functions. [Figure 5C] Absorbance plots of CeO2 quantum dots using UV-Vis-NIR spectroscopy for 14 nm and 5.3 nm CeO2 quantum dots. [Figure 5D] Tauc plot for 14 nm CeO2 quantum dots, with the inset showing a high-resolution TEM micrograph of a single 14 nm CeO2 quantum dot. [Figure 5E] Tauc plot for 5.3 nm CeO2 quantum dots, with the inset showing a high-resolution TEM micrograph of a single 5.3 nm CeO2 quantum dot. [Figure 6] [Figure 6A] Graph showing measured dark current transients for an a-Se (15 μm) / CeO2 quantum dot (150 nm) device over a wide range of applied currents. [Figure 6B] Graph showing measured dark current densities for an a-Se-containing photomultiplier tube according to the present invention including a CeO2 quantum dot hole-blocking layer. [Figure 6C] Graph showing measured optical response for devices with 40 nm and 150 nm CeO2 quantum dot hole-blocking layers achieving avalanche gains of 50 and 7, respectively. The inset shows a schematic of the optical TOF experiment. DETAILED DESCRIPTION OF THE INVENTION

[0019] The present invention will now be described in more detail by reference to the following discussion and drawings that accompany the present invention. It is noted that the drawings of the present invention are provided for illustrative purposes only, and as such, the drawings are not drawn to scale. It is also noted that like and corresponding elements are referred to by like reference numerals.

[0020] In the following description, numerous specific details are set forth, such as particular structures, components, materials, dimensions, processing steps, and techniques, to provide an understanding of various embodiments of the present invention. However, it will be recognized by those skilled in the art that various embodiments of the present invention may be practiced without these specific details. In other instances, well-known structures or processing steps have not been described in detail to avoid obscuring the present invention.

[0021] When an element such as a layer, region, or substrate is referred to as being "on" or "above" another element, it will be understood that it can be directly on the other element, or that intervening elements may also be present. In contrast, when an element is referred to as being "directly on" or "directly above" another element, there are no intervening elements present. When an element is referred to as being "below" or "below" another element, it will also be understood that it can be directly below or below the other element, or that intervening elements may be present. In contrast, when an element is referred to as being "directly below" or "directly below" another element, there are no intervening elements present.

[0022] Embodiments of the invention described herein provide high-gain amorphous selenium photomultipliers and methods of forming same. Embodiments of the invention use high-dielectric-constant solution-processed nanocrystals / nanoparticles (including quantum dots) and / or perovskites as hole-blocking layers to enable high gain to be achieved in amorphous selenium. Embodiments of the invention enable the development of the first true solid-state photomultipliers and the potential to revolutionize solid-state photodetection and imaging, with applications in astronomy, spectroscopy, optical communications, medical imaging, and the rapidly developing fields of quantum optics and quantum information science.

[0023] Amorphous selenium (a-Se) as a solid photoconductive film is poised to revolutionize photodetection through its intrinsic avalanche multiplication process. Two key features of the avalanche phenomenon in a-Se are that, first, only holes heat up and undergo impact ionization, as seen by the large difference between the electron and hole impact ionization rates, and, second, the avalanche process is noiseless and non-Markovian. In addition, a-Se is a large-area, room-temperature semiconductor with a wide bandgap and extremely low leakage current even at high electric fields, and therefore does not require cooling.

[0024] Although a-Se could ideally provide similar gain in a PMT, its avalanche gain has been severely limited in solid-state detector structures by (A) an insulating hole-blocking layer (HBL), or (B) a non-insulating HBL that is non-stoichiometric, or (C) a non-insulating HBL that is stoichiometric but has a low dielectric constant (i.e., 10 or less). The term "stoichiometric" is used herein to define a compound whose components are present in precise proportions according to the formula.

[0025] Item A is inappropriate because the insulator introduces trapped space charge effects and polarization. Item B does not work efficiently because defect states in the HBL substantially enhance charge injection. Item C also limits the achievement of ultra-high gain due to the presence of electric field hot spots near the electrode edges and corners. An alternative HBL is needed for a-Se photomultiplier tubes that can maximize gain and maintain low dark conductivity. The alternative HBL should also achieve reliable and repeatable impact ionization without irreversible breakdown.

[0026] In the present invention, a non-insulating n-type hole-blocking / electron-transporting layer (hereinafter "hole-blocking layer") is provided, which comprises a non-insulating metal oxide. The non-insulating metal oxide has a dielectric constant greater than 10, i.e., the non-insulating metal oxide is a high-k material. The non-insulating metal oxide used as the hole-blocking layer is substantially stoichiometric. By "substantially stoichiometric," it is meant that the non-insulating material oxide is completely stoichiometric or within ±5% of completely stoichiometric.

[0027] The use of such hole-blocking layers in a-Se-containing photomultipliers offers a true solid-state alternative to vacuum PMTs. In the present invention, solution-processed metal oxide nanocrystals / nanoparticles or solution-processed perovskites are used to provide the hole-blocking layer. The solution-processed materials are deposited at temperatures that do not result in crystallization of the a-Se layer (either on the surface or in the bulk). Experimental results of a-Se-containing photomultipliers fabricated using non-insulating high-k metal oxides as hole-blocking layers demonstrate the lowest dark current densities reported to date at avalanche fields, without defect states or oxygen vacancies. The use of low-temperature solution-processed materials as hole-blocking layers may substantially improve the performance of avalanche selenium devices and finally end the long-standing quest to develop solid-state photomultipliers that resemble the behavior of conventional PMTs.

[0028] Referring now to FIG. 1 , a high-gain, low-dark-current-density a-Se photomultiplier tube in accordance with one embodiment of the present invention is illustrated. The a-Se photomultiplier tube of FIG. 1 can be used as a component in a photodetector, imager, sensor, or any other device in which photon detection is desired. The a-Se photomultiplier tube of FIG. 1 includes a substrate 10, a first electrode 12, an electron-blocking layer 14 (i.e., p-layer), an amorphous selenium solid photoconductive film 16 (i.e., i-layer), a passivation buffer layer 18, a hole-blocking layer 20 (i.e., n-layer), and a second electrode 22. In some embodiments, the passivation buffer layer 18 can be omitted. In some embodiments, the substrate 10 can be omitted.

[0029] In the embodiment and as depicted in FIG. 1, a substrate 10, a first electrode 12, an electron blocking layer 14, an amorphous selenium solid photoconductive film 16, a passivation buffer layer 18, a hole blocking layer 20 and a second electrode 22 are stacked vertically in this order.

[0030] If present, the substrate 10 is typically a transparent substrate, such as a semiconductor substrate or a glass substrate. A semiconductor substrate comprises at least one semiconductor material, such as silicon.

[0031] The first electrode 12 can be composed of any transparent conductive material, including, for example, indium tin oxide (ITO). In some embodiments (not shown), the first electrode 12 can be present on the entire substrate 10. In other embodiments, and as depicted in FIG. 1 , the first electrode 12 is present on only a portion of the substrate 10. In some embodiments, the first electrode 12 can be in direct physical contact with the substrate 10, thus forming a material interface therewith. The first electrode 12 can have a thickness of 10 nm to 1000 nm, although other thicknesses for the first electrode 12 are contemplated and can be used. The first electrode 12 can be formed using techniques well known to those skilled in the art. For example, the first electrode 12 can be formed using a deposition process such as physical vapor deposition (PVD), atomic layer deposition (ALD), or plating. In some embodiments, deposition of the transparent conductive material that provides the first electrode 12 can be followed by a patterning process such as photolithography.

[0032] In some embodiments, the electron-blocking layer 14 can be a high-temperature, high-field electron-blocking layer composed of a polymer, such as parylene or polyimide (PI). In other embodiments, the electron-blocking layer 14 is composed of an inorganic electron-blocking material, such as arsenic triselenide (As2Se3) or nickel oxide (NiO). The electron-blocking layer 14 can have a thickness of 10 nm to 6000 nm, although other thicknesses for the electron-blocking layer 14 are contemplated and can be used. The electron-blocking layer 14 can be formed using techniques known to those skilled in the art. For example, the electron-blocking layer 14 can be formed using a deposition process such as chemical vapor deposition (CVD), plasma-plasma-enhanced chemical vapor deposition (PECD), solution deposition, thermal evaporation, or spin-on coating. The electron-blocking layer 14 is typically in direct physical contact with the first electrode 12, thus forming a material interface therewith.

[0033] The amorphous selenium solid photoconductive film 16 is a film of selenium lacking any crystalline structure. While there may be local ordering of atoms within the amorphous selenium solid photoconductive film 16, there is no long-term ordering. The amorphous selenium solid photoconductive film 16 may be doped (stabilized) or undoped. Examples of dopants for the amorphous selenium solid photoconductive film 16 include, but are not limited to, arsenic, tellurium, or chlorine. The dopant may be present in the amorphous selenium solid photoconductive film 16 in an amount of 0.1 atomic percent to 0.5 atomic percent. The amorphous selenium solid photoconductive film 16 may have a thickness of 0.5 μm to 100 μm, although other thicknesses for the amorphous selenium solid photoconductive film 16 are contemplated and may be used as the thickness of the amorphous selenium solid photoconductive film 16. The amorphous selenium solid photoconductive film 16 may be formed using techniques well known to those skilled in the art. In one example, the amorphous selenium solid photoconductive film 16 can be formed by thermal evaporation of stabilized glassy selenium pellets. The amorphous selenium solid photoconductive film 16 is typically in direct physical contact with the electron blocking layer 14, thus forming a material interface therewith.

[0034] If present, the passivation buffer layer 18 is composed of any material that protects the underlying amorphous selenium solid photoconductive film 16 from oxidation. In one example, the passivation buffer layer 18 can be composed of SiO2. The passivation buffer layer 18 can have a thickness of 10 nm to 1000 nm, although other thicknesses for the passivation buffer layer 18 are contemplated and can be used as the thickness of the passivation buffer layer 18. The passivation buffer layer 18 can be formed using deposition, such as sputtering. In the present invention, the deposition of the passivation buffer layer 18 is performed using conditions that do not crystallize portions of the underlying amorphous selenium solid photoconductive film 16 (i.e., neither the surface nor the bulk). Therefore, the amorphous selenium solid photoconductive film 16 remains completely amorphous after the formation of the passivation buffer layer 18. The passivation buffer layer 18 is typically in direct physical contact with the amorphous selenium solid photoconductive film 16, and thus forms a material interface therewith.

[0035] To provide the device with high gain and low dark current density, hole blocking layer 20 comprises a non-insulating metal oxide. The non-insulating metal oxide comprising hole blocking layer 20 has a high-k (i.e., a dielectric constant greater than 10). In some embodiments, the non-insulating metal oxide comprising hole blocking layer 20 has a dielectric constant greater than 10 and up to 100. In other embodiments, the non-insulating metal oxide comprising hole blocking layer 20 has a dielectric constant greater than 10 and up to 20,000. The non-insulating metal oxide comprising hole blocking layer 20 can be substantially stoichiometric, as described above.

[0036] In one embodiment of the present invention, the non-insulating metal oxide forming the hole-blocking layer 20 is composed of metal oxide nanocrystals / nanoparticles. The terms "nanocrystal" and "nanoparticle" are used interchangeably in the present invention. Nanocrystals / nanoparticles typically have a particle size less than 100 nm in diameter. The metal oxide nanocrystals can comprise metal oxide quantum dots. Quantum dots are nanocrystals that demonstrate quantum confinement. Examples of metal oxides that can be used in the present invention as metal oxide nanocrystals / nanoparticles include, but are not limited to, oxides of transition group metals in the periodic table. In one embodiment of the present invention, the metal oxide nanocrystals / nanoparticles used as the hole-blocking layer 20 comprise cerium oxide CeO quantum dots.

[0037] In another embodiment, the non-insulating metal oxide comprising hole-blocking layer 20 is comprised of a perovskite. Perovskites are materials that have the same crystal structure as the mineral titanium calcium oxide. Generally, perovskites have the chemical formula ABX3, where A and B represent cations and X is an anion bonded to both cations. Examples of perovskites that can be used in the present invention include, but are not limited to, strontium titanate (i.e., SrTiO3) or barium titanate (BaTiO3). In one embodiment, the perovskite comprising electron-hole-blocking layer 20 is SrTiO3. Perovskites can also be nanocrystalline.

[0038] Regardless of the type of non-insulating metal oxide used in providing hole blocking layer 20, hole blocking layer 20 can have a thickness of 10 nm to 150 nm, although other thicknesses for hole blocking layer 20 are contemplated and can be used as the thickness of hole blocking layer 20.

[0039] The hole blocking layer 20 of the present invention is formed by first preparing a solution-processed material comprised of metal oxide nanocrystals / nanoparticles or perovskite, as described above. Forming the solution-processed material involves preparing a colloidal dispersion of the metal oxide nanocrystals / nanoparticles or perovskite. The colloidal dispersion further comprises a solvent or solvent mixture. The term "colloidal dispersion" is used herein to refer to a heterogeneous system comprised of a dispersed phase (i.e., metal oxide or perovskite) and a dispersing medium (i.e., solvent or solvent mixture). In a colloidal dispersion, one substance (i.e., metal oxide or perovskite) is dispersed as fine particles in the dispersing medium (i.e., solvent or solvent mixture). The solvent or solvent mixture thus contains the dispersed but insoluble substance, the metal oxide or perovskite. Examples of solvents that can be used in forming the solution-processed material include, but are not limited to, organic solvents, including, for example, hexane, octane, heptane, decane, chloroform, or toluene. In one example, the solution used in providing the solution-processed material comprises a solvent mixture of hexane and octane.

[0040] Preparation of a colloidal dispersion of nanocrystals / nanoparticles or perovskite and a solvent or mixture of solvents involves adding the nanocrystals / nanoparticles or perovskite and the solvent or mixture of solvents in any order. Metal oxide nanocrystals / nanoparticles can be prepared by techniques well known to those skilled in the art. Following the addition step, the metal oxide nanocrystals / nanoparticles or perovskite and the solvent are mixed under conditions that facilitate preparation of the colloidal dispersion.

[0041] After preparing the solution-processed material, it is deposited onto the surface of the amorphous selenium solid photoconductive film 16 at a temperature below the crystallization onset temperature for selenium. By "a temperature below the crystallization onset temperature for selenium" is meant a temperature at which the underlying layer of the amorphous selenium solid photoconductive film 16 does not undergo crystallization, either on the surface of the amorphous selenium solid photoconductive film 16 or within the bulk of the amorphous selenium solid photoconductive film 16, e.g., 80°C or below. Thus, the amorphous selenium solid photoconductive film 16 remains completely amorphous after deposition of the solution-processed material that provides the hole blocking layer 20. In one embodiment, deposition of the solution-processed material that provides the hole blocking layer 20 is performed at a temperature of 60°C or below. In yet another embodiment, deposition of the solution-processed material that provides the hole blocking layer 20 is performed at nominal room temperature (i.e., a temperature of 20°C to 30°C).

[0042] Deposition of solution-processed materials that provide hole blocking layer 20 can include any well-known deposition technique, including, but not limited to, spray coating, spin coating, inkjet printing, doctor blading, roll-to-roll printing, dip coating, screen printing, drop casting, brush painting, stamp printing, zone casting, hollow pen writing, slot die coating, or solution shearing.

[0043] In some embodiments of the present invention, the deposited solution-processed material can be subjected to a ligand exchange process to provide the hole blocking layer 20. The ligand exchange process involves replacing the native ligands used during synthesis and deposition with new organic and inorganic ligands, which are typically, but not necessarily always, compact, short-chain ligands. This ligand exchange process can be performed before or after deposition. Typical short-chain ligands can be organic, such as ethanedithiol, ethyleneamine, pyridine, hydrazine, or inorganic, such as sulfides, hydroxides, selenides, tellurides, thiocyanates, hydrosulfides, and the like.

[0044] The second electrode 22 can be composed of any transparent conductive material, including, for example, indium tin oxide (ITO). The transparent conductive material comprising the second electrode 22 can be compositionally the same as or different from the transparent conductive material comprising the first electrode 12. In one embodiment, both the first electrode 12 and the second electrode 22 are composed of indium tin oxide. In some embodiments (not shown), the second electrode 22 can be present on the entire hole-blocking layer 20. In other embodiments, and as depicted in FIG. 1 , the second electrode 22 is present on a portion of the hole-blocking layer 20. In some embodiments, the second electrode 22 can be in direct physical contact with the hole-blocking layer 20, thus forming a material interface therewith. The second electrode 22 can have a thickness of 10 nm to 1000 nm, although other thicknesses for the second electrode 22 are contemplated and can be used. The second electrode 22 can be formed using techniques well known to those skilled in the art. For example, the second electrode 22 can be formed utilizing a deposition process such as, for example, physical vapor deposition (PVD), atomic layer deposition (ALD), or plating. In some embodiments, deposition of the transparent conductive material that provides the second electrode 22 can be followed by a patterning process such as, for example, photolithography.

[0045] The following examples are provided to illustrate some aspects of the present invention, but the present invention is not limited by the following examples.

[0046] Example I Amorphous selenium (a-Se) photomultiplier tubes containing different hole-blocking layers.

[0047] In this example, the electric field and effective quantum efficiency were investigated for various vertical a-Se photomultipliers containing different hole-blocking layers. Specifically, the various vertical a-Se photomultipliers contained amorphous selenium as the photoconductive film 16, different hole-blocking layers 20, as defined below, and an indium tin oxide second electrode 22.

[0048] The different hole-blocking layers 20 include a 100 nm SiO hole-blocking layer (k=4) for FIG. 2A (not of the present invention), a 100 nm CeO quantum dot hole-blocking layer (k=28) for FIG. 2B (of the present invention), and a 100 nm SrTiO hole-blocking layer (k=300) for FIG. 2C (of the present invention), where k=ε r Note that the SiO hole-blocking layer was deposited by sputtering, while the CeO quantum dot hole-blocking layer and the SrTiO hole-blocking layer were prepared by first providing a solution-processed material and then depositing the solution-processed material at a temperature below the crystallization onset temperature for selenium.

[0049] Referring now to Figures 2A, 2B, and 2C, plots of the electric field within various a-Se photomultiplier tubes are shown. Note that in all cases, the electric field within the bulk is 100 V / μm. As shown in Figure 2A, electric field hotspots existed when using a SiO hole-blocking layer. In Figure 2B, electric field hotspots existed when using a CeO hole-blocking layer, but to a lesser extent than when using a SiO hole-blocking layer. For example, when using a CeO hole-blocking layer, the electric fields near the electrode / oxide and oxide / a-Se interfaces reach 300 V / μm and 200 V / μm, respectively, while the bulk is biased at only 100 V / μm. As shown in Figure 2C, electric field hotspots are completely eliminated when using a SrTiO hole-blocking layer.

[0050] Referring now to Figure 3, the effective quantum efficiency of various a-Se photomultipliers is shown, where the avalanche gain is severely limited due to the presence of electric field hot spots. However, using a SrTiO3 hole-blocking layer, the quantum efficiency is reduced to 10 6 A high gain of 1000kJ / s was achieved.

[0051] Example II Investigations using solution-processed CeO2 quantum dots as a hole-blocking layer.

[0052] In this example, a solution-processed CeO quantum dot layer with a large bandgap of 3.77 eV was deposited on an a-Se photoconductor at room temperature without surface or bulk crystallization. Figure 4A shows a schematic of the p-i-n structure and a transverse focused ion beam scanning electron microscope (FIB-SEM) of the fabricated prototype, showing the p-i-n and ITO electrode layers. With particle sizes less than the exciton Bohr radius of 7–9 mm, CeO quantum dots exhibit quantum confinement effects and a size-tunable bandgap, further increasing the hole potential barrier beyond 2.8 eV. Many previously reported CeO quantum dot syntheses required high-temperature calcination (500–600 °C), resulting in non-stoichiometric CeO and prone to morphological instability and uncontrolled aggregation. Here and in this example, we demonstrate a facile colloidal approach to obtain quantum-confined, ligand-passivated, substantially stoichiometric, non-aggregated CeO quantum dots ranging from 14 nm to 5.3 nm, with bandgaps ranging from 3.66 eV to 3.77 eV, respectively. The colloidal CeO quantum dots were synthesized using the high-temperature decomposition approach proposed by Runnerstrom et al. in "Colloidal Nanocrystal Films Reveal the Mechanism for Intermediate Room Temperature Proton Conductivity in Porous Ceramics," J. Phys. Chem. C208, 122, 13624-13635.

[0053] Figure 4B shows a transmission electron microscope (TEM) image of a collection of fairly monodisperse quantum dots with an average particle size of 5.3 ± 0.7 nm (Figure 4C). The inset in Figure 4C shows a high-resolution TEM micrograph of a single CeO quantum dot with a 0.316 nm interplanar spacing measured from the lattice fringes, corresponding to the (111) plane of cubic fluorite.

[0054] To establish a clearer physical picture of the light interactions in a-Se avalanche photodetectors with bulk CeO quantum dot hole-blocking layers, device-level simulations were performed using SILVACO TCAD (ATLAS version 5.25.1.R). Figure 4D shows the simulated energy band diagrams for the detector structure at different electric fields, where the transport transitions from a localized to an extended state after the avalanche threshold voltage (≈80 V / μm) is exceeded, resulting in hole-induced avalanche gain.

[0055] The powder X-ray diffraction pattern of the CeO2 quantum dots, shown in Figure 5A, is consistent with the cubic fluorite structure of CeO2, with Scherrer broadening resulting in broad peaks. As the average particle size increases from 5.3 nm to 14 nm, the diffraction peaks sharpen, as expected. To elucidate the oxidation state and stoichiometry of CeO2, the Ce3d emission spectrum was studied using X-ray photoelectron spectroscopy (XPS). 4+ and Ce 3+ The coexistence of both is illustrated in Figure 5B. 3+ and Ce 4+ The spectrum in Figure 5B is deconvoluted because the peaks of Ce almost overlap each other, so 3+ The concentration of Ce was estimated to be a nontrivial value of 18.5%, which is approximately 10% to 20% lower than previously reported values ​​for CeO2 quantum dots synthesized through other methods. 3+ leads to oxygen vacancies, thereby creating defect states in the quantum dots. In the colloidal approach of the present invention, ligands are used both to provide colloidal stability and to passivate defects. Moreover, these surfactants can induce quantum dot-ligand interface dipoles that are responsible for energy level shifts in the valence band maximum, thus potentially increasing the hole barrier even further.

[0056] The band gap of the as-synthesized CeO quantum dots was measured via UV-Vis-NIR absorption spectroscopy (Figure 5C). The absorption spectrum of the quantum dots dispersed in carbon tetrachloride did not exhibit clear absorption peaks at the band edges. Therefore, the band gap was calculated from the experimental data using Tauc plots, which demonstrated that as the size of the quantum dots decreased from 14 nm to 5.3 nm, the optical direct band gap increased from 3.66 eV to 3.77 eV (Figures 5D and 5E), as expected from quantum confinement effects.

[0057] Because the colloidal dispersibility of the as-synthesized quantum dots in this approach was enhanced by the ligands, devices could be fabricated at room temperature using inexpensive deposition techniques such as inkjet printing or spin-coating. 5.3 nm CeO2 quantum dots with a bandgap of 3.77 eV were spin-coated onto 110 nm SiO2 a-Se substrates at room temperature, achieving CeO2 quantum dot layers of 40 nm and 150 nm thickness.

[0058] The quality of thin quantum dot films deposited from the colloidal approach according to the present invention was compared with that of a precipitation method using custom-made CeO2 quantum dots according to the procedure of Arul et al., entitled "Strong Quantum Confinement Effect in Nanocrystalline Cerium Oxide," Mater. Lett. 2011, 65, 2635-2638. The colloidally synthesized CeO2 quantum dots with ligands achieved uniform deposition without microcracks, voids, or aggregation of the quantum dots, clearly highlighting the importance of appropriate surfactants in achieving better colloidal dispersions for thin film fabrication.

[0059] As-synthesized CeO quantum dots with long-chain ligands were exchanged with short-chain NHSCN ligands in the deposited thin films to increase the electronic coupling in the quantum dots on true solid-state devices, and the ligand exchange was followed using Fourier transform-infrared spectroscopy (FT-IR). The peak at 2048 cm after the ligand exchange corresponds to NHSCN. -1The appearance of a distinct peak at ≈88% indicates that approximately 88% of the ligand exchange has occurred. It was concluded from XRD that the solution treatment of the present invention did not initiate crystallization on a-Se.

[0060] Figure 6A illustrates the measured dark current density transients of a 150 nm thick CeO quantum dot-based pin device over a wide range of applied electric fields, E. In each case, the transients were fit with a biexponential (solid line) until a steady state (dotted line) was reached after 25 min. The rapid initial drop in dark current is due to injected carriers being trapped within the hole-blocking layer, lowering the effective E at the interface, while the second gradual decay to steady-state equilibrium is due to the detrapping of bulk space charge.

[0061] Figure 6B illustrates the measured dark current density of devices according to the present invention (40 nm green and 150 nm blue) as a function of E at 1 minute (dotted line) and 30 minutes (solid line), comparing the transient and steady-state dark currents. At subavalanche fields (E<70 V / μm), the steady-state dark current of a device according to the present invention with a 150 nm CeO quantum dot layer is 30 pA / cm. 2 At the high electric fields required for avalanche gain, the dark current was measured to be extremely low, approximately 50 pA / cm at E = 88 V / μm. 2 reached.

[0062] Figure 6B also compares the dark current density for solid-state a-Se avalanche devices fabricated with the nip sequence, adapted from Ohshima et al., "Excess Noise in Amorphous Selenium Avalanche Photodiodes," Appl. Phys., Part 2 1991, 30, L1071-L1074, and Abbaszadeh et al., "Investigation of Hole-Blocking Contacts for High-Conversion-Gain Amorphous Selenium Detectors for X-Ray Imaging," IEEE Trans. Electron Devices 2021, 59, 2403-2409. In each case, the measured steady-state dark current after the onset of avalanche (E > 70 V / μm) was at least two orders of magnitude lower than the solid-state nip a-Se avalanche device. Additionally ... 3 Dark current values ​​from a vacuum HARP image pickup tube capable of achieving a gain of 100 Ω / s are also fitted and included for comparison. While low-field data are not available for the vacuum HARP device, results are extended (dashed line) utilizing the same impact ionization curve as Park et al., entitled "Avalanche-type High Sensitive Image Pickup Tube using an a-Se photoconductive target," Jpn. J. Appl. Phys. 2003, 42, L209-L211, demonstrating the significant potential improvement in sensitivity at high fields if similar gains are achieved with devices according to the present invention. Each of the fitted nip HARP results shown in Figure 6B utilized a CeO2 hole-blocking layer deposited via high-temperature vacuum deposition. CeO2 films utilized in nip devices are incompatible with the nip fabrication sequence, have defect levels due to oxygen vacancies, and generally exhibit poor performance as a function of increasing film thickness. Experimental results for pin devices according to the present invention showed the lowest reported dark current density at avalanche fields, with over 300% improvement over best-in-class solid-state vertical devices and almost 200% improvement over even vacuum devices.

[0063] Unlike bulk CeO2, the results provided by Figure 6B show a substantial decrease in dark current with increasing CeO2 film thickness, which can be hypothesized as follows: (i) the colloidal synthesis method results in relatively low intensity CeO2 in the XPS spectrum; 3+ The peaks indicate that a small number of CeO quantum dots at the surface induce discrete localized defect states. This result is consistent with the fact that the formation energy of "intrinsic" defects in quantum dots is typically much larger than in the bulk, thus suppressing defect formation. (ii) The presence of sparse, isolated defects in thin films does not strongly interact with each other and does not form continuous defect bands within the band gap, even with increasing film thickness. The majority of defects in these quantum dots are relegated to the surface, with each quantum possessing a defect state (if any) at random energy states, generating a random dispersion of energy states with an extremely low density of states rather than a coherent band. (iii) Ammonium thiocyanate ligands could potentially passivate surface defect states resulting from oxygen vacancies through dative bonding. However, the significant reduction in dark current clearly promises the potential application of low-temperature solution-processed quantum dots as hole-blocking layers.

[0064] Figure 6C illustrates the photoresponse of devices with 40 nm (green) and 150 nm (blue) CeO quantum dot hole-blocking layers, achieving avalanche gains of 50 and 7, respectively. The inset in Figure 6C schematically represents the optical time-of-flight (TOF) photoconductivity experiment used to measure the photoresponse of each sample as a function of E. The effective quantum efficiency η* was measured over a wide range of electric fields (E = 6-100 V / μm). At subavalanche electric fields, photogeneration efficiency is limited by geminate recombination. However, as E increases, the probability of recombination decreases as electron-hole pairs are more efficiently separated, increasing η* until a steady state is reached, following the Onsager dissociation model. Once the avalanche threshold is crossed, η* increases rapidly as the hole drift mechanism shifts from localized trap-limited mobility to extended-state zonal transport, resulting in impact ionization of holes, thereby liberating additional EHPs and thus amplifying the signal current. The maximum applied electric field before electrical breakdown (E≈120V / μm) resulted in an avalanche gain of ≈50.

[0065] In conclusion, this example demonstrates that the use of low-temperature solution-processed quantum dots as a hole-blocking layer can substantially improve the performance of pin avalanche a-Se detectors and end the long-standing quest to develop solid-state photomultiplier tubes that resemble the behavior of conventional PMTs.

[0066] Synthesis of CeO2 quantum dots All chemicals were used as purchased without purification. 5.3 nm CeO colloidal quantum dots (QDs) were synthesized using a modified procedure proposed by Runnerstrom et al. (see J. Phys. Chem. C208, 122, 13624-13635). In a typical synthesis, 8 ml of oleylamine and 5 ml of 1-octadecene were added to 868.4 mg of Ce(NO3)3. 6H2O was added to a 250 ml round-bottom, three-neck flask at room temperature. The temperature was then raised to 80 °C and held constant for 30 min to homogenize the reaction mixture. The temperature was then raised again to 250 °C and maintained for 2 h, resulting in the decomposition of the precursor and the nucleation and growth of QDs. During the above process, the stopper was punctured with a needle to avoid overpressure in the flask due to the release of nitrogen dioxide (NO2) gas during the decomposition of Ce(NO3)3. After 2 hours, the common surfactant oleic acid (typically about 1% by volume of the reaction mixture) was added to improve colloidal stability and minimize aggregation. The reaction mixture was then annealed at 250 °C for an additional 5 minutes and then air-cooled to room temperature. Ethanol was added to the resulting reaction mixture as an anti-solvent and centrifuged at 8500 rpm for 5 minutes to crush the QDs. The collected QDs were dispersed in 5 ml of hexane, after which oleic acid (about 10% by volume of the mixture) was added and stirred overnight. The purification process was repeated three times using redispersions in ethanol and hexane. The as-synthesized QDs were dispersed in an 8:2 solvent ratio of hexane and octane to form 30 mg / ml and 50 mg / ml colloidal dispersions for further use in thin film fabrication. To study the effects of quantum confinement, large-sized CeO2 colloidal quantum dots (approximately 14 nm) were synthesized according to the procedure described by Runnerstrom et al. (See J. Phys. Chem. C208, 122, 13624-13635). 40 mg of octadecylamine, 4.9 ml of oleylamine, and 5 ml of octadecene were added to a 250 ml round-bottom three-neck flask under a nitrogen stream and heated to 70 °C to melt the octadecylamine. 4342.4 mg of Ce(NO3)3.6H2O and 0.725 ml of deionized water were added to the reaction mixture.The mixture was heated to 175°C and then annealed for 30 minutes to achieve homogeneity, after which the temperature was increased to 230°C. After 2 minutes at 230°C, a large amount of NO2 was released and evaporated, indicating the completion of the reaction. The resulting solution was then air-cooled. To avoid overpressurization of the flask, the stopper was punctured with a needle, as previously described. The collected colloidal solution was washed with ethanol and hexane, similar to the process utilized for the 5.3 nm CeO2 quantum dots.

[0067] Device fabrication Each avalanche device is 2.5 x 2.5 in 2 We utilized a pin fabrication process developed for ITO-coated glass substrates. The p-layer was deposited directly onto the ITO-coated glass under high vacuum. The p-layer consisted of a 2 μm thermally evaporated inorganic electron-blocking layer, followed by thermal evaporation of stabilized glassy selenium pellets to form a 15 μm a-Se i-layer. A 110 nm film of low-temperature sputtered SiO2 (provided by Hionix Inc.) was deposited over the a-Se surface as a passivating buffer layer. Solution-synthesized CeO2 quantum dots, as described above, were spin-coated at room temperature to form the n-layer. A 30 mg / ml dispersion of CeO2 quantum dots was spin-coated at 2000 rpm for 45 seconds, and a similar 50 mg / ml dispersion was spin-coated at 1700 rpm for 45 seconds. The combined CeO2 quantum dot films were ligand exchanged with a 130 mM (1% w / v) solution of ammonium thiocyanate (NH4SCN) in acetone, followed by spin-coating of pure acetone with the same spin parameters as CeO2 to remove unbound NHClSCN.

[0068] The thin-film deposition and ligand exchange of CeO2 quantum dots was repeated twice to achieve the desired thickness. Transparent ITO high-voltage electrodes were patterned using a shadow mask and deposited via oxygen-assisted electron beam deposition. Following completion of wire bonding to the ITO-based readout and high-voltage electrodes, the entire device was encapsulated with parylene to prevent high-voltage effects on the top surface.

[0069] Photoconductivity measurements For each measurement, a CAEN N1471A programmable high-voltage power supply was used to positively bias the top electrode of the avalanche a-Se device. Time (I) and voltage (I-V)-dependent dark current characteristics were measured with a Keithley 6514 electrometer. Charge transport characteristics and avalanche gain were measured through optical time-of-flight transient experiments using a 450 nm pulsed LED source with a 170 ns FWHM, driven by a Tektronix AFG3021B function generator. Stimulated photocurrent was captured with a Tektronix TDS7104 digital oscilloscope. A Tektronix P6245 active probe was utilized to protect against device breakdown at high electric fields. For all photocurrent measurements of avalanche gain, the a-Se device was mounted in a light-shielded, grounded metal box.

[0070] While the present invention has been particularly shown and described with reference to preferred embodiments thereof, it will be understood by those skilled in the art that these and other changes in form and detail may be made therein without departing from the spirit and scope of the invention. It is therefore intended that the present application not be limited to the exact forms and details described and illustrated, but fall within the scope of the appended claims. [Explanation of symbols]

[0071] 10 Substrate 12 First electrode 14 Electron blocking layer 16. Amorphous selenium solid photoconductive film 18 Passivation buffer layer 20 Hole blocking layer 22 Second electrode

Claims

1. an electron blocking layer provided on the first electrode; an amorphous selenium solid photoconductive film provided on the electron blocking layer; a hole blocking layer disposed on the amorphous selenium solid photoconductive film, the hole blocking layer comprising a non-insulating metal oxide having a dielectric constant greater than 10, being substantially stoichiometric, and selected from transition metal oxides or perovskites having a chemical formula of ABX 3 , where A and B represent cations and X is an anion bonded to both cations, the transition metal oxide and the perovskite both being nanocrystalline having a grain shape with a diameter of less than 100 nm; a second electrode provided on the hole blocking layer; A photomultiplier element comprising:

2. The photomultiplier element of claim 1 , further comprising a passivation buffer layer sandwiched between the amorphous selenium solid photoconductive film and the hole blocking layer.

3. The photomultiplier element according to claim 1 , wherein the first electrode is provided on a surface of a substrate.

4. The photomultiplier element of claim 1 , wherein the first electrode, the electron blocking layer, the amorphous selenium solid photoconductive film, the hole blocking layer and the second electrode are vertically stacked in order.

5. 2. The photomultiplier element according to claim 1, wherein the amorphous selenium solid photoconductive film is completely amorphous.

6. The photomultiplier element of claim 1, wherein the transition metal oxide comprises cerium oxide quantum dots.

7. The photomultiplier element of claim 1 , wherein the perovskite comprises strontium titanate or barium titanate.

8. At least one photomultiplier element, the at least one photomultiplier element comprising: an electron blocking layer provided on the first electrode; an amorphous selenium solid photoconductive film provided on the electron blocking layer; a hole blocking layer disposed on the amorphous selenium photoconductive film, the hole blocking layer comprising a non-insulating metal oxide having a dielectric constant greater than 10, being substantially stoichiometric, and selected from transition metal oxides or perovskites having the chemical formula ABX3, where A and B represent cations and X is an anion bonded to both cations, the transition metal oxide and the perovskite both being nanocrystalline having grain shapes less than 100 nm in diameter; and a second electrode disposed on the hole blocking layer.

9. 9. The device of claim 8, further comprising a passivation buffer layer sandwiched between the amorphous selenium solid photoconductive film and the hole blocking layer.

10. The device of claim 8, wherein the transition metal oxide comprises cerium oxide quantum dots.

11. 9. The device of claim 8, wherein the perovskite comprises strontium titanate or barium titanate.

12. 1. A method of forming a photomultiplier element, comprising the steps of: forming an electron blocking layer over the first electrode; forming an amorphous selenium solid photoconductive film on the electron blocking layer; forming a hole blocking layer on the amorphous selenium solid photoconductive film, the hole blocking layer comprising a non-insulating metal oxide, the non-insulating metal oxide having a dielectric constant greater than 10, being substantially stoichiometric, and selected from transition metal oxides or perovskites having a chemical formula of ABX3, where A and B represent cations and X is an anion bonded to both cations, the transition metal oxide and the perovskite both being nanocrystalline with grains less than 100 nm in diameter; forming a second electrode on the hole blocking layer.

13. forming the hole blocking layer, Preparing a solution-processed material comprised of metal oxide nanocrystals or perovskites; and depositing the solution-processed material on a surface of the amorphous selenium solid photoconductive film at a temperature below a crystallization onset temperature for selenium.

14. 14. The method of claim 13, wherein the solution processing material comprises a colloidal dispersion of cerium oxide nanocrystals, deposition of the colloidal dispersion of cerium oxide nanocrystals provides a layer of cerium oxide quantum dots, and the layer of cerium oxide quantum dots is further subjected to a ligand exchange process to form the hole blocking layer.

15. The method of claim 13 , wherein the temperature of the deposition is nominally room temperature.